2017
DOI: 10.1161/circulationaha.117.028430
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitor Therapy

Abstract: Background PCSK9 inhibitors (PCSK9i) are a novel class of medications for patients with familial hypercholesterolemia or clinical atherosclerotic cardiovascular disease (ASCVD) requiring additional lipid lowering beyond dietary measures and statin use. Because of the drugs' high cost, rates of prescription approval by payers may be low. We aimed to identify payer approval and rejection rates for PCSK9i prescriptions, and potential factors influencing these rates. Methods This is a retrospective, descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Overall, the implementation of a dedicated PCSK9i clinic has resulted in a 97% rate of drug approval, far higher than the national average approval rate of 40–50% reported in the literature. 912 Financial burden for patients was very reasonable in most cases, with an average monthly out-of-pocket expenditure of $57 and discontinuation rates due to cost of only 2.3%. This high approval rate and low patient out-of-pocket expenditure stands in contrast with media reports and the peer-reviewed literature in which about a third of patients were reported never filling PCSK9i prescriptions primarily due to cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the implementation of a dedicated PCSK9i clinic has resulted in a 97% rate of drug approval, far higher than the national average approval rate of 40–50% reported in the literature. 912 Financial burden for patients was very reasonable in most cases, with an average monthly out-of-pocket expenditure of $57 and discontinuation rates due to cost of only 2.3%. This high approval rate and low patient out-of-pocket expenditure stands in contrast with media reports and the peer-reviewed literature in which about a third of patients were reported never filling PCSK9i prescriptions primarily due to cost.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports of PCSK9i treatment have provided details from either the clinical trial perspective, 4–6 the provider perspective, 712 or the payer and societal perspectives. 1318 However, few reports have reflected the patient experience with PCSK9i in clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake of PCKS9 inhibitors, however, has been marred by its high cost-currently between USD 5000 and USD 14,000 per year of treatment, which may last for the rest of the patient's life. This has been shown to be not cost-effective (Korman et al 2018), and many insurers decline to cover it (Hess et al 2017). Access, then, will depend in large part on the ability of patients to afford the high out-of-pocket costs of the treatment.…”
Section: Balancing Of Interests/sharing Of Benefitsmentioning
confidence: 99%
“…A high-burden PA process may be related to high rates of rejection for submitted PCSK9i prescriptions because other studies have reported that commercial payers also had the lowest PA approval rates. 2,3 Why are we examining the intricate details of the PCSK9i PA process and high rejection rates? The reason is clear-simply put, these drugs are expensive and at a level not previously seen for a drug with this potentially large of a market.…”
mentioning
confidence: 99%
“…In evaluations of current populations that might be eligible for PCSK9i, more than half of eligible patients were not receiving statin therapy, which clearly represents a deficiency in optimal risk reduction management. 2,3 Oftentimes, excitement surrounding the uptake of new drugs drives potential overuse, even in the absence of outcomes evidence, with subsequent difficulty with reining in prescribing in all but the strictest of formularies. 8 Abandonment of existing effective therapies may also ensue, and this seems to be the case with the excitement surrounding PCSK9i.…”
mentioning
confidence: 99%